PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI SIKLUS AIR DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Zahra, Fatimahtu; Aprilia, Rapita; Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The goal of this project is to create an animated film about the water cycle for use in primary school science classes. The purpose of this study was to determine the outcomes of practicality as well as the validation of material experts, language experts, and media experts. Analysis (Analysis), Design (Planning), Development (Development), Implementation (Implementation), and Evaluation (Evaluation) are the five stages of the ADDIE model, which is the sort of R&D used in this study. Observation, interviews, expert validation questionnaires, and student and teacher response surveys are the methods utilized to gather data. Linguists received a percentage of 97.7% with the criteria